2019
DOI: 10.9734/ijpss/2019/v29i330146
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilizers Effect on Potato (Solanum tuberosum L.) Tuber Production in Sandy Loam Soil

Abstract: Potatoes are one of the most common and important vegetable crops in the world and carrying different health benefits that make them all the more essential as a staple dietary item for much of the world’s population. The high nutrient content, ability to adapt to marginal environments, relative ease of cultivation and low cost and high productivity are attributes that make potatoes one of the principal and most important sources of food and income for developing countries. Considering the importance of organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
4
2
0
1
Order By: Relevance
“…Growth and yield enhancement of potato crop such as increased plant height, number of branches, number of tuber, weight and yield of tuber etc. from combined manure and fertilizer application were also reported by many researchers (Jaipaul et al 2011, Venkatasalam et al 2012, Balemi 2012, Amara and Mourad 2013, El-Sayed et al 2014, Ahmadiet al 2014, Shaheen et al 2014, Suh et al 2015, Masrie et al 2015, Hafez et al 2017, Koireng et al 2018, Bekele et al 2018, Ahmed et al 2019. The results of the present experiments are either fully or partially accorded to the above mentioned comparable studies.…”
Section: Resultssupporting
confidence: 90%
“…Growth and yield enhancement of potato crop such as increased plant height, number of branches, number of tuber, weight and yield of tuber etc. from combined manure and fertilizer application were also reported by many researchers (Jaipaul et al 2011, Venkatasalam et al 2012, Balemi 2012, Amara and Mourad 2013, El-Sayed et al 2014, Ahmadiet al 2014, Shaheen et al 2014, Suh et al 2015, Masrie et al 2015, Hafez et al 2017, Koireng et al 2018, Bekele et al 2018, Ahmed et al 2019. The results of the present experiments are either fully or partially accorded to the above mentioned comparable studies.…”
Section: Resultssupporting
confidence: 90%
“…The increase due to the animal compost may be attributed to its role in improving chemical, physical and microbial properties of the soil that increases absorption of water and utilization of nutrients and thus vegetative growth parameters if potato, also, animal compost may give balance micro and macronutrients just as upgraded accessibility of plant nutrients, which would assist with upgrading the metabolic activity of microorganisms and improvement of plant growth. This results are in agreement with the findings of other researchers who observed that animal compost increased growth of potato (Ahmed et al 2019;Alemayehu et al 2020;.…”
Section: Vegetative Growth Parameterssupporting
confidence: 94%
“…The positive effect of manure used combined with mineral fertilization on potato yielding was confirmed in many previous studies [ 42 , 43 , 44 ]. Beneficial effect of manure on the content of organic matter contributes to increasing water retention, reducing soil erosion and improving the physicochemical and biological properties of the soil [ 45 ].…”
Section: Resultssupporting
confidence: 77%